El problema de definición de la perífrasis verbal en español (dudas y contradicciones) - Lisyová, Ol'ga (Studia Romanica Posnaniensia, 2004)
The theme of this contribution originated from contradictory understanding of the conception of periphrastic verbal constructions by different linguists. In spite of the fact that most of the grammars consider as being periphrastic the constructions consisting of a rigid form of the full-meaning verb (infinitivo, gerundio, participio pasado), they diverge in the definition of the auxiliary verb. We discuss the substantiation to name various verbal constructions as periphrastic. We come from the basic definition of the periphrasis as a descriptive expression, the semantic significance of which is formed by a synthesis of its constituents, but not by the constituents themselves.